Study on failure modes of a new staggered story isolated structure based on IDA method - Chen, Lihao; Wang, Taize; Wang, Qinyue; Liu, Dewen; Xiao, Zhiyi; Liao, Gengjie; Yang, Zhuoxin; Lei, Min (Frontiers in Earth Science, 2023)
New staggered story isolated structure is a new type of isolated system. This paper explores the failure mode of a new staggered story isolated structure with the increment dynamic analysis (IDA) method. On the basis of a finite model of a new isolated structure with staggered stories, a failure criterion for isolated structure was established. The findings indicate that the new staggered, isolated structure has good collapse resistance. When the story angle limit is 1/100, the primary structure will fail before the isolated layer in the event of a strong earthquake, and failure typically happens at the base of the structure where components with a higher bearing capacity should be used. Under the impact of the P-δ effect, the upper isolated layer is more prone to failure than the lower isolated layer. The upper isolated layer may have a tensile stress exceeding 1MP and a horizontal displacement exceeding 385 mm, which may lead to the risk of structural overturning. Therefore, higher strength supports should be selected for the weak position of the isolated layer.